2019
DOI: 10.2478/pielxxiw-2019-0008
|View full text |Cite
|
Sign up to set email alerts
|

Nursing dress code and perception of a nurse by patients

Abstract: Introduction. Professional image of the nurse in the opinion of the patient community is conditioned by many variables, including professional attire. A worthy representation of the nurse profession is the responsibility of all those who care for the patient.Aim. Determining the impact of dress code on shaping the professional image of nurses in the opinion of patients.Material and methods. Non-systematic review method of the literature available. The data was obtained by searching online databases, such as: G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…11,18,[31][32][33] Other nonresearch articles included 2 case studies, 8,16 a legal commentary, 34 2 specific to nursing issues, 10,17 and an editorial. 35 Also included were 2 literature reviews, 13,15 a policy development piece, 14 an evidence-based practice (EBP) project, 36 and EBP recommendations. 37 Through independent analysis of the articles by 2 nurse researchers, followed by iterative team discussions, 3 broad themes and 8 subthemes emerged (see Supplemental Digital Content, Figure 2, available at: http://links.lww.com/NE/B83): (1) level of acceptability (subthemes of positive perception, stigmatizing, and personal meaning); (2) professional image (subthemes of appearance matters and policy); and (3) infection concern (subthemes of hygiene, contamination, and injury potential).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…11,18,[31][32][33] Other nonresearch articles included 2 case studies, 8,16 a legal commentary, 34 2 specific to nursing issues, 10,17 and an editorial. 35 Also included were 2 literature reviews, 13,15 a policy development piece, 14 an evidence-based practice (EBP) project, 36 and EBP recommendations. 37 Through independent analysis of the articles by 2 nurse researchers, followed by iterative team discussions, 3 broad themes and 8 subthemes emerged (see Supplemental Digital Content, Figure 2, available at: http://links.lww.com/NE/B83): (1) level of acceptability (subthemes of positive perception, stigmatizing, and personal meaning); (2) professional image (subthemes of appearance matters and policy); and (3) infection concern (subthemes of hygiene, contamination, and injury potential).…”
Section: Resultsmentioning
confidence: 99%
“…Professional image was exemplified in the subthemes of appearance matters and policy through 7 of the 9 research articles [22][23][24][25][26][27][28] and 16 of the 21 nonresearch articles. 7,[9][10][11][12][13][14][15][16][17][18]32,[34][35][36] Nurses' appearance conveys professionalism, trustworthiness, confidence, and compassion. 27,28 Research linked nurses' professional image and patients' perceptions of competency in care and comfort with the care provided.…”
Section: Theme 2: Professional Imagementioning
confidence: 99%
See 2 more Smart Citations
“…As nursing students discussed, one potential way to help build trust with the community is by wearing their uniforms to demonstrate their professional status. Previous studies have shown how the nurse uniform is associated with trust among patients (Küçük et al., 2015; Pawlowski et al., 2019). While insider status provides certain benefits, it also creates potential blind spots.…”
Section: Discussionmentioning
confidence: 99%